Predictive value of CD3+ cells and interleukin 2 receptor in systemic inflammatory response syndrome after percutaneous nephrolithotomy - He, Yu; Xia, Ding; Tong, Yonghua; Shang, Haojie; Liu, Xiao; Peng, Ejun; Huang, Qiu; Tang, Kun; Chen, Zhiqiang (Frontiers in Immunology, 2022)
Abstract Objective: The aim of current study was to evaluate risk factors that influence the development of postoperative systemic inflammatory response syndrome (SIRS) after percutaneous nephrolithotomy (PCNL), including cytokines and lymphocyte subsets. Methods: One hundred and fifty-four patients who underwent PCNL at our hospital between October 2018 and January 2022 were retrospectively reviewed. The development of post-PCNL SIRS was the primary endpoint of the study. Univariable analysis and multivariable logistic regression analysis were performed to identify independent risk factors of post-PCNL SIRS. A nomogram was constructed using the independent risk factors and receiver operating characteristic (ROC) curves were drawn. Results: Fifty patients (32.5%) developed SIRS after PCNL. In multivariate analysis positive urine culture (odds ratio [OR] 3.556, P = 0.048,), long operation time (OR 1.011, P = 0.027), high IL-2R (OR 1.002, P = 0.018), low percentage of CD3+ cells (OR 0.931, P = 0.006) and high white blood cell (WBC) count (OR 1.282, P = 0.044) were independent risk factors for post‐PCNL SIRS. These five significant variables were used to generate a nomogram that exhibited favorable fitting. The discrimination area under the ROC curves was 0.795. Conclusions: Patients with long operation times, positive urine cultures, high interleukin 2 receptor, high white blood cell counts, and low percentages of CD3+ cells may be at higher risk of developing SIRS after PCNL. In these patients, cautious and comprehensive p